Potential of oleochemicals waste to serve as partial sand replacement in concrete - Amy Syahiera, Abdul Malik (2019)
The production of oleochemicals waste (sludge) from palm oil through chemical process is increasing over past few years. Disposal of sludge has brought towards serious environmental problem. At the same time, the growing of construction industry has lead towards the increasing in sand mining activities which pose adverse impact towards the environment as it lowers the stream bottom of the river. In an effort to use the sludge in large volume and to reduce sand mining activities, this research is carried out for its possible in making concrete containing sludge as partial sand replacement. The experimental investigation is performed to evaluate the strength and water absorption of concrete mixtures, in which sand is replaced with 0%, 5% and 10% of sludge by weight of sand. The sludge is oven dried at 100°C for not more than 24 hours after collected from the factory and then the dried sludge are grinded and sieved before mixing. All the mixes were cast in form of cubes and prisms and then subjected to air curing and water curing until the testing date. From the results, it is observed that the combination of sludge content would affect the strength and rate of absorption of the concrete. Samples produced using 5% and 10% sludge as partial sand replacement has not achieved optimum strength compared to control concrete due to the concrete sample are fragile and easily broken since there are presence of polymers in the sludge, while the rate of absorption cannot be recorded as there is corrosive effect on the surface of the sample when the sample is submerged in the water.